4. Musical Skills in the Artistic Knowledge Process - Crișciuc Viorica (Sciendo, 2020)
The article hereby includes conceptual aspects of the musical competences formation. It describes the realization of this process operating with the concepts of well-known occidental, Russian and local researchers. One of the ideas characteristic to the researchers' pedagogical thinking is that, during the process of musical competence formation through art, the acquisition process mechanism is happening. For integrity in insuring the practical realization at of a musical education, the methodology we propose is based on research, an imposing theoretical network of successful pedagogical practices of remarkable scientists from all over the world. The analyzed theories are a source of inspiration and constitute the theoretical universe which contributes to as truthful as possible musical education.